Facile Synthesis of a Fluorinated‐Squaramide Covalent Organic Framework for the Highly Efficient and Broad‐Spectrum Removal of Per‐ and Polyfluoroalkyl Pollutants. (21st June 2022) - Huang, Junlong; Shi, Yueru; Huang, Guo‐zhang; Huang, Shuyao; Zheng, Juan; Xu, Jianqiao; Zhu, Fang; Ouyang, Gangfeng
Abstract: The escalating contamination by per‐ and polyfluoroalkyl substances (PFAS) has become an urgent issue in recent years, and the structural diversity of PFAS is the major challenge for effective pollution control. Herein, we take the intrinsic advantages of squaramide and prepare a new two‐dimensional covalent organic framework (FSQ‐1) that exhibits broad‐spectrum PFAS affinity. The tailor‐made linker forges hydrogen‐bond donors, hydrogen‐bond acceptors, and fluorophilic segments into one framework. The obtained material exhibits multipoint and multitype affinity to PFAS with different structures, by which high‐efficient and broad‐spectrum removal of various PFAS can be simultaneously achieved. Notably, the thermodynamic profiles provided by isothermal titration calorimetry (ITC) experiments further illustrate the underlying mechanism of the broad‐spectrum affinity. FSQ‐1 can also be applied for efficient PFAS extraction in trace‐level PFAS analysis. Abstract : At the intersection of molecular recognition and materials science, a multi‐functional two‐dimensional covalent organic framework (COF) is prepared and applied as a broad‐spectrum adsorbent for the high‐efficiency removal of per‐ and polyfluoroalkyl pollutants.